ENHANCING RELIABILITY AND EFFICIENCY OF DETECTING MALICIOUS DATA INJECTION IN WIRELESS SENSOR NETWORKS: AN IN-DEPTH ANALYSIS - Shrivastava, Vinay; Bhatele, Mukta; Waoo, Akhilesh A. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Wireless sensor networks (WSNs) have gained significant attention in recent years due to their versatile applications ranging from wildlife tracking to environmental monitoring. However, WSNs are susceptible to various challenges such as hardware failures, communication link faults, and malicious attacks, which can significantly affect their reliability and performance. In this paper, we focus on the issue of malicious data injection in WSNs and propose a survey to explore its impact on network security and performance.